The Effect Of Investment Return And Accounting Literacy On Interest In Investing In The Capital Market - Ayem, Sri; Langkodi, Hiskia (Universitas Muhammadiyah Pontianak, 2025)
This study investigates the effect of investment return and accounting literacy on students’ interest in investing in the capital market. Using a quantitative approach, 110 economics students in Yogyakarta were selected through simple random sampling. Data were analyzed using multiple regression. Results show that investment return and accounting literacy significantly and positively influence investment interest. These findings highlight the importance of strengthening financial education and providing accessible information about potential investment returns to encourage greater participation in the capital market, particularly among young investors seeking to achieve long-term financial goals and improve decision-making capabilities.